First-principles simulation of elastic constants and electronic properties of GaN - Sambrano, Julio Ricardo [UNESP]; Toniatto, Elen C. M. [UNESP] (Bentham Science Publishers, 2014)
The electronic and structural properties and elastic constants of the wurtzite phase of GaN, was investigated by computer simulation at Density Functional Theory level, with B3LYP and B3PW hybrid functional. The electronic properties were investigated through the analysis of the band structures and density of states, and the mechanical properties were studied through the calculus of the elastic constants: C11, C33, C44, C12, and C13. The results show that the maximum of the valence band and the minimum of the conduction band are both located at the Γ point, indicating that GaN is a direct band gap semiconductor. The following constants were obtained for B3LYP and B3PW (in brackets): C11 = 366.9 [372.4], C33 = 390.9 [393.4], C44 = 99.1 [96.9], C12 = 143.6 [155.2], and C13 = 107.6 [121.4].
Keywords: GaN; Elastic constant; B3LYP; B3PW; Periodic calculations